Effects of infection history on dengue virus infection and pathogenicity - Tim K. Tsang (Nature Portfolio, 2019)
Lack of knowledge of individual infection history hinders understanding of immunological interactions among DENV serotypes. Here, the authors introduce a framework to infer the relationship between unobserved infection history and subsequent infection and disease risk, and find complex dependencies.